Attachment, perceived social support and mental health problems in women with primary infertility - Saleem, Sadia; Qureshi, Namra S.; Mahmood, Zahid (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Infertility is one of the fastest growing concerns when it comes to reproductive health and most often, women get the blame. Consequently, females suffer from major psycho-social and emotional problems that may lead to serious mental health concerns. Methods: To fill the gap in literature, a cross-sectional research design was used to measure the attachment styles with spouse, perceived social support, and predict mental health problems in women attending infertility clinics with ages ranging from 19-45 (M 27.21, SD 4.79). Adult Attachment Questionnaire, Multidimensional Perceived Social Support, and Depression Anxiety Stress Scale were used among experimental subjects selected through purposive sampling technique. Results: About 32% women reported themselves as secure, 49% as ambivalent, and 19% as avoidant in their attachment style with spouse. The results revealed that a significant negative correlation exists between perceived social support and mental health problems among women with infertility. Moreover, women who identify their attachment pattern as Ambivalent perceive less social support and experience more mental health problems. Conclusions: Education is one of the strongest predictors of how likely infertility is to cause mental health issues while Attachment style is another strong indicator since infertile women with secure attachment pattern have fewer mental health problems. However, the sample size was modest to make any wide-scale assumptions, so further trials with larger participant pools must be performed. Additionally, future studies should include both rural and urban samples with different psychological variables to find the similarities and differences between various groups of people with diverse backgrounds.